Computational assessment of disbond growth behaviour in adhesively bonded wide joints or patch repairs for primary airframe structures - Veldyanto Tanulia; John Wang; Garth M. Pearce; Alan Baker; B. Gangadhara Prusty (Composites Part C: Open Access, 2022)
This paper evaluates the applicability of a damage slow growth management strategy to patch repairs or bonded joints of primary aircraft structures established earlier by the authors utilising wide bonded metal joints through a computational study using MSC Marc software. The adhesive element failure criteria was applied to establish the residual static strength of the joint as a function of disbond length. A cohesive zone element model implemented in a Ucohesive subroutine was used to evaluate the strain energy release rates (SERRs) as a function of disbond crack extent and predict the disbond growth in the joint. Similar to the 2D analysis conducted in the past, the results showed that for a wide joint with sufficient static strength safety margin under a typical fatigue loading that would propagate disbond, the disbond growth would be stable within a particular length range. Therefore, the slow growth approach would be viable when the patch is modelled to be large enough to allow expanded damage growth. Furthermore, numerical results on the load redistribution effect indicate an overall significantly slower disbond growth and longer fatigue life of the joint with part width disbond than that with full-width disbond.